Effectiveness Learning Differentiate to Creativity and Motivation Learn the Attention, Relevance, Confidence and Satisfaction Model (ARC)To Students Class VI of Inpres Elementary School MaponuSarjoDistrict, Regency wood installation - Affandi; Hasan; Idrus (Kirana Publisher (KNPub), 2025)
Paradigm in curriculum independent characterized by Student - centered and student - centered learning . Student - centered learning contain meaning that the learning process must be put student as object constructivist learner​ understanding through the information obtained from various source Study with help facilitation learning by teachers. Formulation problem study Whether learning differentiate effective in increase creativity and motivation learning ARCS model in students Class VI at SD Inpres Maponu . Research objectives This that is Analyze effectiveness learning differentiate to creativity and motivation learning ARCS model in students Class VI at SD Inpres Maponu . Research methods quantitative is research process​ Lots use numbers from start data collection , interpretation to the data, as well as appearance the results . Research results This is Instrument questionnaire consists of from 28 grains statement that has been through the validation process expert conducted by Mr. Dr. Sunarto Amus , M.Si as validator lecturer . The results of the validation process the show that the entire instrument will used declared valid according to with criteria that have been set . After declared valid, then the instrument is tested return For measure its validity in non - groups is sample study with use Product Moment formula .